2003
DOI: 10.1163/156856003322699555
|View full text |Cite
|
Sign up to set email alerts
|

Dexibuprofen: pharmacology, therapeutic uses and safety

Abstract: Dexibuprofen is the single pharmacologically effective enantiomer of rac-ibuprofen. Racibuprofen and dexibuprofen differ in their physico-chemical properties, in terms of their pharmacological properties and their metabolic profiles. Several clinical trials and post-marketing surveillance studies were performed to broaden the findings on dexibuprofen. In the last 5 years 4836 patients have been exposed to dexibuprofen in clinical trials and PMS trials. Only in 3.7% of patients adverse drug reactions have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 17 publications
1
53
0
7
Order By: Relevance
“…The influence of concomitant diseases on the extent of inversion remains largely unexplored. Furthermore, it was shown that the metabolism of S -ibuprofen is cleaner and R -ibuprofen might contribute to adverse effects as shown in a be thanechol-induced gastric irritation model [14] . The removal of R -ibuprofen does not involve lipid metabolism and, in contrast to conventional ibuprofen, which underlies variable chiral inversion, S -ibuprofen avoids variability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The influence of concomitant diseases on the extent of inversion remains largely unexplored. Furthermore, it was shown that the metabolism of S -ibuprofen is cleaner and R -ibuprofen might contribute to adverse effects as shown in a be thanechol-induced gastric irritation model [14] . The removal of R -ibuprofen does not involve lipid metabolism and, in contrast to conventional ibuprofen, which underlies variable chiral inversion, S -ibuprofen avoids variability.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of R -ibuprofen decreased the potency of S -ibuprofen much more than theoretically expected [25] . Bridging studies versus conventional ibuprofen and studies versus other NSAIDs including celecoxib confirm the good relative efficacy and tolerability profile of dexibuprofen [14,[16][17][18] . Results from clinical trials demonstrate that at a dose ratio of 0.5: 1 dexibuprofen is at least equally effective and safe as conventional ibuprofen [14,[16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ibuprofen, a non-selective NSAID, is a racemic mixture of the S-and R-enantiomer [7] . The two enantiomers differ in terms of their pharmacological properties, and may be regarded as two individual active pharmaceutical moieties.…”
Section: Introductionmentioning
confidence: 99%